A science-based product regulation: the time has come to reduce toxic emissions to reduce harm - Kunze, Michael; Santin, José Roberto; Kunze, Ursula (Frontiers in Public Health, 2025)
Tobacco control has focused on reducing use, with little emphasis on regulating product toxicity. Articles 9 and 10 of the World Health Organization's Framework Convention on Tobacco Control (FCTC) offer a mechanism to reduce harm by limiting toxic emissions, but implementation has stalled. A science-based regulatory framework is needed to set emission thresholds for toxicants. Inspiration can be found from other regulated sectors, and the initial focus should be on nine priority toxicants strongly linked to tobacco-related disease. An adaptive, evidence-based approach can complement existing strategies and accelerate harm reduction for more than 1 billion people who still smoke. The 11th FCTC Conference of the Parties in 2025 presents an opportunity to revisit the development of a toxicity reduction strategy.